1996
DOI: 10.1111/j.1365-2788.1996.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Respondent and informant accounts of psychiatric symptoms in a sample of patients with learning disability

Abstract: This paper investigates differences in the nature and frequency of psychiatric symptoms reported by patients with learning disability and key informants. The study involved psychiatric assessment of 100 patients with learning disabilities and key informants using the Psychiatric Assessment Schedule for Adults with a Developmental Disability (PAS-ADD), a semi-structured psychiatric interview developed specifically for people who have a learning disability. There was considerable disagreement between respondent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 6 publications
1
27
0
1
Order By: Relevance
“…Improving on record reviews, some researchers make DSM or ICD diagnoses based on direct interviews of children with intellectual disability or their parents (e.g., Bouras et al, 1994 ;Moss, Prosser, Ibbotoson, & Goldberg, 1996). It bodes well for future prevalence studies that the most recent versions of these systems, the DSM-IV and ICD-10, are more alike than different (Volkmar & Shwab-Stone, 1996).…”
Section: Issues Of Psychiatric Diagnosesmentioning
confidence: 99%
“…Improving on record reviews, some researchers make DSM or ICD diagnoses based on direct interviews of children with intellectual disability or their parents (e.g., Bouras et al, 1994 ;Moss, Prosser, Ibbotoson, & Goldberg, 1996). It bodes well for future prevalence studies that the most recent versions of these systems, the DSM-IV and ICD-10, are more alike than different (Volkmar & Shwab-Stone, 1996).…”
Section: Issues Of Psychiatric Diagnosesmentioning
confidence: 99%
“…Murphy (1994) stated that for people with mild intellectual disability who can communicate their feelings and beliefs, it is possible to diagnose mental health problems accurately and, while this may at times co-exist with challenging behaviour, the two are not necessarily causally related (Holland & Murphy 1990). However, a psychiatric disorder is much more difficult to diagnose accurately (Murphy 1994) when subjects have profound and multiple intellectual disabilities, and are unable to communicate their feelings, and there is a high dependency on third-person reports (Moss et al 1996). Therefore, it can be difficult to recognize mental health problems in people who have an intellectual disability, and there is a risk of underdiagnosis and the attribution of symptoms to intellectual disability per se (Dosen 1993).…”
Section: Challenging Behaviour and Mental Healthmentioning
confidence: 99%
“…It has been suggested by some researchers that this population is at a higher risk of health problems because of a sedentary lifestyle combined with high rates of obesity (Rimmer et al 1993;Beange et al 1995;Robertson et al 2000). In addition, adults with intellectual disabilities may have dif®culties reporting symptoms (Beange et al 1995), caregivers may not know what symptoms should be reported to physicians (Moss et al 1996) and physicians may be untrained to work with this population (Lennox et al 1997).…”
Section: Introductionmentioning
confidence: 99%